1989
DOI: 10.1017/s0022029900028880
|View full text |Cite
|
Sign up to set email alerts
|

Composition and structure of micellar calcium phosphate

Abstract: Micellar calcium phosphate has the chemical composition and physicochemical properties that are consistent with it being a complex of the phosphate centres of casein with an acidic amorphous calcium phosphate. Similar acidic amorphous calcium phosphates have been prepared in the laboratory and for these, as well as for micellar calcium phosphate, the most appropriate crystalline model compound from which the short-range structure may be derived is brushite, CaHPO 4 .2H 2 O. The predicted secondary structures a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 16 publications
3
28
0
1
Order By: Relevance
“…There is a close similarity in salt and peptide composition, solubility, size, and structure between casein-calcium phosphate nanoclusters prepared in the laboratory with casein phosphopeptides and the sequestered ACP in native bovine casein micelles, strongly suggesting that most caseins are cemented into the micelle by links through their PC to an acidic ACP (Holt et al, 1989). The successful ab initio calculation of the salt partition in bovine milk confirms the correctness of this assumption (Holt, 2004).…”
Section: Safe Secretion Of High Concentrations Of Calcium and Phosphatementioning
confidence: 61%
See 1 more Smart Citation
“…There is a close similarity in salt and peptide composition, solubility, size, and structure between casein-calcium phosphate nanoclusters prepared in the laboratory with casein phosphopeptides and the sequestered ACP in native bovine casein micelles, strongly suggesting that most caseins are cemented into the micelle by links through their PC to an acidic ACP (Holt et al, 1989). The successful ab initio calculation of the salt partition in bovine milk confirms the correctness of this assumption (Holt, 2004).…”
Section: Safe Secretion Of High Concentrations Of Calcium and Phosphatementioning
confidence: 61%
“…It predicts successfully, among other things, the partition of milk salts and the fraction of each of the caseins that is bound through one or more of its PC to the sequestered ACP. It also resolves the apparent paradox that the sequestered ACP is a basic salt in composition but an acidic salt according to its solubility behavior (Holt et al, 1989;Holt, 2004). An explicit expression for the equilibrium radius of the sequestered ACP nanoclusters has also been derived (Holt et al, 2009).…”
Section: Casein Micelle Structurementioning
confidence: 68%
“…Previous studies have shown (Holt 2004, Holt et al 1989) that the composition of micellar calcium phosphate is consistent with that of an acidic ACP. High-resolution electron microscopy (Lyster et al 1984) of dried samples of micellar calcium phosphate showed that longer-range order did not extend over distances more than ~1.5 nm.…”
Section: Introductionmentioning
confidence: 79%
“…Une partie est liée directement aux groupements phosphoséryls des caséines, l'autre est présente sous forme de phosphate de calcium et assure la cohésion de la micelle. La nature chimique de ce phosphate de calcium étant encore discutée (eg Holt et al, 1989;Van Dijk, 1990), nous avons retenu l'hypothèse d'un phosphate de calcium colloïdal tricalcique sous forme amorphe (Schmidt, 1982) L'évolution des pourcentages de calcium et de phosphore inorganique solubles semble traduire un transfert progressif de constituants de la phase soluble vers la phase colloïdale au fur et à mesure de l'avancement de la période de production. On peut émettre l'hypothèse que l'augmentation de la teneur en caséine du lait, alors que les concentrations en calcium et phosphore inorganique restent relativement stables, entraîne un certain déficit minéral des micelles qui se traduit par un déplace-ment des équilibres salins au profit de la phase colloïdale.…”
Section: Conformémentunclassified